KARAKTER KIMIA PUPUK CAIR ASAL LIMBAH KULIT PISANG KEPOK DAN PENGARUHNYA PADA TINGGI TANAMAN KEDELAI - Nurul Puspita Palupi (Universitas 17 Agustus 1945 Samarinda, 2015)
Chemical Character of Banana Skin Waste Liquid Fertilizer and their influences for the soya beans plant’s height. MOL is a collection of microorganisms that can be developed, which serves as a starter in the bokasi or compost production. Utilization of agricultural waste such as fruit unfit for consumption is processed into MOL could increase the added value of waste, and reduce environmental pollution (Juanda, et al., 2011). MOL utilization in organic farming is still much to do, especially soybeans. Data from the Central Bureau of Statistics According to the BPS 2013 said the soybean production in 2013 was 807 568 tons of dry beans and the amount of production is decreased when compared to production in 2012, is about 843 153 tonnes. The high consumption of soy as a feedstock would cause Indonesia still imports of processed soybean.This study was conducted from March to June 2015 lies in the Laboratory of Soil Science, Faculty of Agriculture University Mulawarman. The experimental design used completely randomized design (CRD), four replication, with doses as follows: 0 ml MOL kepok banana peel / plant (p0 as control), 100 ml MOL kepok banana peel / plant (p1), 200 ml MOL kepok banana peel / plant (p2), 300 ml MOL kepok banana peel / plant (p3), dan 400 ml MOL kepok banana peel / plant (p4).The results showed that the content of nutrient elements in the solution is not sufficient to meet the needs of soybean plant growth, high visible from plants that are not significantly different from the control treatment. MOL solution of kepok banana peel also not qualify on SNI liquid fertilizer.